Credit to pioneering work on carbon nanotubes - Eugene A Katz (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2021)
This letter gives a credit to a pioneering paper by A. M. Nesterenko, et al. (Izvestia Akademii Nauk SSSR, Met. 1982, [in Russian]) that is almost unknown to scientific community. On the basis of Transmission Electron Microscopy images and X-ray Ray Diffraction patterns of "carbon multi-layer tubular crystals" the authors suggested a model of nanotube structure formation and hypothesis on various chirality of carbon nanotubes.